India - Himachal Pradesh : Accelerating Development and Sustaining Success in a Hill State - World Bank (Washington, DC, 2012)
This Economic Report is the first by the World Bank on the economy of Himachal Pradesh (HP), and the first on a hill state in India. HP is a unique state in many respects-most importantly because of the enormous success it has achieved over the past three decades, despite severe structural disadvantages of relative remoteness, environmental fragility, and a difficult hill terrain, characteristic of Himalayan states in India. The study sets out to document, first, the remarkable success that the state has achieved in terms of sustained growth and human development, and the underlying reasons in terms of supportive policies and social cohesion. In this respect, HP makes an important contribution to lessons of success for the other nine Himalayan hill states in India. The second, and more extensive part of the Report, is forward-looking. It describes how it might be possible to build on the past success that HP has achieved, and, at the same time, address some crucial economic and social transitions that will be essential for the state to firmly secure its future: (i) a sustained increase in income levels along with an enabling environment for the private sector; (ii) the creation of suitable jobs based on enhanced productivity and skill s of its young labor force that can shift from public to private sector employment; and (iii) the utilization of natural resources like hydropower, forests, and water resources wisely and well. There is every reason to be confident that HP can meet these challenges. The state's past enviable track record is testimony to the ability of its people and leadership to forge a social consensus and compact necessary to achieve such goals. The Report seeks to provide an analysis of HP's current economic situation, and to lay out a menu of reform options that can help build on HP's considerable strengths and opportunities, and address some of the main challenges ahead.